Respuesta :
If a + b = 2a, then
a + b - 2a = 2a - 2a
b + a - 2a = 2a - 2a
b - a = 2a - 2a = 0
Therefore, b - a = 0.
a + b - 2a = 2a - 2a
b + a - 2a = 2a - 2a
b - a = 2a - 2a = 0
Therefore, b - a = 0.
ANSWER
C.
[tex]0[/tex]
EXPLANATION
The given equation is
[tex]a + b = 2a[/tex]
We make b the subject to get,
[tex]b = 2a - a[/tex]
This simplifies to,
[tex]b = a[/tex]
Subtracting
[tex]a[/tex]
from both sides will give us,
[tex]b - a = a - a[/tex]
The right hand side will now simplify to zero,
Therefore
[tex]b - a = 0[/tex]
C.
[tex]0[/tex]
EXPLANATION
The given equation is
[tex]a + b = 2a[/tex]
We make b the subject to get,
[tex]b = 2a - a[/tex]
This simplifies to,
[tex]b = a[/tex]
Subtracting
[tex]a[/tex]
from both sides will give us,
[tex]b - a = a - a[/tex]
The right hand side will now simplify to zero,
Therefore
[tex]b - a = 0[/tex]